On the Influence of Vulnerable Marine Ecosystem Habitats on Peracarid Crustacean Assemblages in the Northwest Atlantic Fisheries Organisation Regulatory Area - Ashford, Oliver S.; Kenny, Andrew J.; Barrio Froján, Christopher R. S.; Downie, Anna-Leena; Horton, Tammy; Rogers, Alex D. (Frontiers in Marine Science, 2019)
Vulnerable marine ecosystems (VMEs) are considered hotspots of biodiversity and ecosystem functioning in the deep sea, but are also characterised by a high vulnerability to disturbance and a low recovery potential. Since 2006, a series of United Nations General Assembly resolutions have been developed, attempting to ensure the protection of VMEs in international waters. In the Northwest Atlantic Fisheries Organisation (NAFO) Regulatory Area, large areas of seabed have been closed to bottom-contact fishing to protect VMEs. However, knowledge of the influence of VME-indicator taxa on macrofaunal assemblages, and the appropriateness of current fishery closures for protecting macrofaunal biodiversity in this area is limited. Here we investigate relationships between the prevalence of VME-indicator taxa (poriferans [sponges], gorgonian corals and pennatulaceans [sea pens]) and an extensive suite of peracarid crustacean biodiversity metrics in the NAFO Regulatory Area. We also examine whether the current NAFO VME closures protect areas of significantly elevated peracarid diversity. Of the VME-indicator taxa analysed, poriferans were found to have by far the greatest influence over peracarid assemblages. Assemblage structure was altered, and peracarid abundance, biomass, richness, diversity, and variability were enhanced in areas of elevated poriferan biomass, whilst assemblage evenness was slightly depressed in these areas. These findings reaffirm the perception of poriferans as crucial components of VMEs. In contrast, gorgonian coral density had little influence over the faunal assemblages investigated, perhaps reflecting their relatively low prevalence in the study area. Similarly, pennatulaceans were found to influence peracarid assemblages only weakly. This too may reflect a moderately low density of Pennatulacea in the study area. Our results highlight that the application of taxon distribution model outputs to ecological investigations and management decisions in data-limited environments should be treated with caution. Finally, our results indicate that the current system of fishery closures in the NAFO Regulatory Area may not be optimal in terms of providing adequate protection to VMEs against the impacts of bottom trawling.